Tailoring the morphology in Y2O3 doped melt-grown Al2O3/ZrO2 eutectic ceramic. (1st March 2017) - Fu, Liansheng; Fu, Xuesong; Chen, Guoqing; Han, Wen-bo; Zhou, Wenlong
Abstract: The addition of more components are an interesting way of the microstructural controls. Herein, adding Y2 O3 to Al2 O3 -ZrO2 bulk eutectic at the low G / v ratio (thermal gradient G divided by growth rate v ) was adopted to tailor the morphology. As the Y2 O3 content increases, the solidification structure changes obviously from cellular into the dendritic shape. Especially, a typical irregular Al2 O3 /ZrO2 /Y3 Al5 O12 (YAG) ternary eutectic appeared in the inter-colony region for the higher Y2 O3 content. This microstructure transition is consistent with the classical constitutional supercooling criterion. Graphical abstract: